The Impact of National Culture Dimensions on Multidimensional Work Ethics Portfolio: A comparative Study on Three Samples from Iraq, India and South Korea - Aalyasin, Mohamed (The Arab Journal of Administration, 2021)
In recent years, several applied researches have been conducted to examine ethical beliefs across different cultures. Some scholars and researches believe that ethics depends on culture, and that the national culture dimensions can predict the desired ethical standards in a particular society. Accordingly, this study aims to explore the impact of National Culture Dimensions (NCD) on Multidimensional Work Ethics Portfolio (MWEP). The study adopted six national culture dimensions presented by Hofstede in his studies (1980, 1991, and 1994) and its revised version of 2013, and the multidimensional work ethic portfolio presented by (Miller et al. 2002) and its developer measure. The study sample was randomly selected (356) respondents in three countries (105) from Iraq, (136) from India and (115) from South Korea. The results of the study highlighted the impact of the national culture dimensions on multidimensional work ethics portfolio. But, the level of impact varied among the three countries. In addition, the results of comparison showed statistically significant differences among countries in national culture dimensions and in work ethic dimensions, while no significant differences were found among the level of the same country, either in national culture dimensions or in multidimensional work ethic portfolio.